Study of the Amplitude of Accommodation and its Relation to Errors of Refraction: A Hospital Based Study - Chaudhary, Neha Priyadarshani; Gautam, Pramod Sharma; Dahal, Sagar; Acharya, Devendra (Journal of Nobel Medical College, 2018)
Background: The unique ability of the eye to vary the refractive power of the lens and to focus on things at a range of distances is called accommodation. The reduction of this ability in which the near point recedes further away from comfortable reading distance is called presbyopia. There is continuing research to understand this process and correct this affliction that affects each and every person at the peak of their productive life. With an aging population, the proportion of people above 40 years is on the rise. This will therefore have public health and economic implications. Materials and Methods: This is a hospital based retrospective study which was conducted in 100 presbyopic patients in age group of 35 to 60 years at outpatient department of ophthalmology in Nobel Medical College and Teaching Hospital, Biratnagar, from 1st October 2016 to 30th March 2017. The amplitude of accommodation was calculated by measuring near point of accommodation with the help of RAF rule and the data collected was subjected to statistical analysis. Results: Out of 100 patients in this study who visited our OPD with presbyopic complains, the no. of hypermetropic patients were highest (56%) and they presented with presbyopic symptoms at an early age as compared to myopes, while the no. of myopic patients were less(13%) and they presented late with presbyopic symptoms. The mean amplitude of accommodation was highest in myopes in all age group (3.35 D in 36-40 year age group which reduced to 2.65 D in 56-60 year age group).There was stastistically significant difference in amplitude of accommodation between myopia and hypermetropia in all age groups except in 56-60 year age group. Conlusion: The amplitude of accommodation is generally higher in myopes in all age groups as compared to hypermetropes and emmetropes and they usually develope presbyopic symtoms later in life.